2004
DOI: 10.1172/jci20106
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic approach for hemophilia using gene delivery of an engineered secreted activated Factor VII

Abstract: Hemophilia is a bleeding disorder caused by mutations in the genes encoding coagulation Factor VIII (FVIII) or FIX. Current treatment is through intravenous infusion of the missing protein. The major complication of treatment is the development of neutralizing Ab's to the clotting factor. Infusion of recombinant activated human Factor VII (rhFVIIa), driving procoagulant reactions independently of human FVIII (hFVIII) or hFIX, has been successful in such patients and could in theory provide hemostasis in all he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 44 publications
(24 reference statements)
4
67
0
Order By: Relevance
“…In an effort to bypass these drawbacks, we have previously demonstrated that a factor VII transgene engineered to be secreted in its activated form (FVIIa) can correct the hemostatic parameters in mouse models of hemophilia A (HA) and B (HB), after either adeno-associated viral (AAV) vector delivery 9 or in transgenic animals. 10 However, a necessary step preceding human application is the demonstration of safety and efficacy in a large animal (canine) model.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to bypass these drawbacks, we have previously demonstrated that a factor VII transgene engineered to be secreted in its activated form (FVIIa) can correct the hemostatic parameters in mouse models of hemophilia A (HA) and B (HB), after either adeno-associated viral (AAV) vector delivery 9 or in transgenic animals. 10 However, a necessary step preceding human application is the demonstration of safety and efficacy in a large animal (canine) model.…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of the transgene reached up to 1000 ng/ml with the highest vector dose injected and didn't induce any thrombotic complications but still corrected phenotype [31,32]. In contrast, the overexpression at levels greater than 2 µg/ml caused mortality and pathological changes in heart and lung [33].…”
Section: Preclinical Fviia Gene Therapy Studiesmentioning
confidence: 99%
“…The enhanced GFP and the ATP7B molecule, identical to the coding sequence of human isoform a (GenBank reference sequence NM_000053.2), were inserted into the HIV-1-based transfer vector, a modified FG12 plasmid, 32 under the transcriptional control of a LSP, which contained elements of apolipoprotein E and alpha-1 antitrypsin, making it hepatocyte specific. 33 The transgene cassette contained the enhanced green fluorescent protein, eGFP reporter (Clontech) or both the reporter and the full-length ATP7B cDNA molecule. Bicistronic expression was achieved by inserting the therapeutic gene in-frame with the eGFP cDNA and the TaV sequence, a cis-acting hydrolase element derived from Thosea asigna virus.…”
Section: Lentiviral Vector Designmentioning
confidence: 99%